Immunohistochemical expression of VDR is associated with reduced integrity of tight junction complex in psoriatic skin. (15th September 2014) - Visconti, B.; Paolino, G.; Carotti, S.; Pendolino, A.L.; Morini, S.; Richetta, A.G.; Calvieri, S.
Abstract Background Cell junctions are crucial for the formation and maintenance of the paracellular barrier and for cell polarity in simple epithelia and endothelia. Altered localization and formation of tissue junction proteins in the epidermis have been described in plaque‐type psoriasis. Vitamin D receptor (VDR) is a nuclear hormone involved in anti‐proliferative and pro‐differentiation pathways in keratinocytes. However, still to date, vitamin D/VDR signalling involved in tissue barrier related to psoriasis remains largely unknown. Objective To study the expression of VDR and tight junctions (TJ) proteins (claudin 1, ZO‐1 and occludin) in psoriatic skin, and to correlate the expression of VDR with that of the junctional proteins claudin‐ 1, occludin and ZO‐ 1. Methods A total of 20 psoriatic tissue samples were included in the analysis. Immunohistochemical studies for VDR, claudin‐1, occludin and ZO‐1 were performed. Results We observed a reduction of VDR, claudin‐1 and ZO‐1 expression in psoriatic skin if compared to normal skin, and the statistical analysis showed a significant correlation between a downgrading of VDR expression and that of claudin‐1 (P < 0.005) and ZO‐1(P < 0.005). Conclusions Our results suggest a new role of VDR in the maintenance of the homeostasis skin barrier. Although the exiguity of our cohort, VDR status appears to be associated with the expression level and functions of TJ proteins, suggesting multiple and different cellular functions of the VDR.